"I’m happy that I get to study this language, and it’s part of my culture" : The well-being of Sámi children and the realisation of their rights - Weckström, Elina; Kekkonen, Karri; Kekkonen, Outi (fi=Lapsiasiavaltuutetun toimisto|sv=Barnombudsmannens byrå|en=Office of the Ombudsman for Children|, 2023)
The purpose of the survey was to examine the well-being of Sámi children and the realisation of their rights in the words of the children themselves. The results of this survey provide up-to-date information, for example to decision-makers and the Sámi community, to support decision-making, development and other activities. The survey was carried out in 2022 by the Office of the Ombudsman for Children as part of the National Child Strategy. It was taken by children aged 11–17 who identify as Sámi, both from the Sámi Homeland and other parts of Finland. The key results of the survey were 1) Sámi children’s strong relationship with nature and concern over the effects of climate change on northern nature; 2) challenges in mobility and access to services in sparsely inhabited areas; 3) opportunities to use the Sámi language and 4) Sámi identity and rights. Summaries in North Sámi, Inari Sámi, Skolt Sámi, Finnish, and Swedish. The cover page was updated on 30 May 2023 (a typo corrected) and this version replaces the previous one published on 6 April 2023.